Sociometric Status in Bullying Perpetrators: A Systematic Review - Cañas, Elizabeth; Estevez, Estefania; Estevez, Jesus F. (Frontiers in Communication, 2022)
Numerous studies have analyzed the relationship between sociometric status and bullying but it is difficult to reach a consensus regarding this issue. Objective The present study carried out a systematic review on the sociometric status of adolescent bullies. Design The bibliographic search was carried out in the mainly databases. Results The findings of 29 studies selected defend three positions. First, bullying is associated with the popular status in their peer group. Second, rejected or unpopular adolescents tend to perpetrate bullying as a response to the frustration generated by their status. Finally, other group the perpetrators of bullying is among these two poles. Conclusions The students' sociometric status is necessary for designing bullying intervention programs at school.